Isobaric vapor-liquid equilibrium data for the binary systems of dimethyl carbonate with xylene isomers at 93.13 kPa - Yadav, S.S. (Journal of Chemical and Engineering Data, 2017)
Isobaric binary vapor-liquid equilibrium (VLE) data for dimethyl carbonate with xylene isomers (p-xylene, m-xylene, o-xylene, and ethylbenzene) were measured at the local atmospheric pressure of 93.13 kPa by using a dynamic recirculation still. The experimental VLE data were tested and found to be thermodynamically consistent by Herington and Van Ness consistency test. The experimental VLE data were correlated using the Wilson, NRTL, and UNIQUAC activity coefficient models and binary interactions parameters were estimated using a suitable objective function. The absolute mean deviation between the experimental and the model predicted values of vapor phase composition and total pressure was well within acceptable limits. No azeotrope was observed in any of the binary pairs and appeared to be easy for separation using conventional distillation method.
Keywords: Atmospheric Pressure; binary mixture; Distillation; Xylene

Thermodynamic Analysis of EMISE– water as a working pair for absorption refrigeration system - Takalkar, G. D.; Bhosale, R. R.; Mali, N. A.; Bhagwat, S. S. (Applied Thermal Engineering, 2019)
In this paper, thermodynamic analysis of novel ionic liquid 1 Ethyl-3-methylimidazolium ethyl sulphate (EMISE) as absorbent and water as green refrigerant for absorption refrigeration system (ARS) is performed. Thermodynamics excess properties like excess Gibbs free energy (GE), excess enthalpy (hE) and equilibrium Dühring's plot (P-T-x1) of EMISE-H2O binary mixture are assessed using non-random two liquid (NRTL) activity coefficient model for composition x1 of 0.45–1. The performance of single effect ARS with SHE are mathematically modeled and simulated by applying first and second laws (exergy analysis) of thermodynamics. Simulated results of ARS are compared with other widely used working fluids and revealed higher COP of 0.66 for EMISE-H2O in comparison to NH3-H2O but lower than LiBr-H2O. In addition, the deviation in the COP and ECOP with the generator temperatures are compared for the evaporation temperature of 5, 10, 15 °C. Result showed noticeable difference between the optimum generator temperature based on COP and ECOP. This indicates the exergy analysis is used for evaluation of ARS and selection of heat source supply temperature obtained from waste heat and renewable solar energy.